Urgency Analysis of Cursive Writing in Strengthening Literacy of Grade IV Students at Elementary School - Makhali; Annisah Nurul Dzulaekha; Ahmad Triyo Laksono; Erna Yayuk (Universitas Islam Negeri Palopo, 2026)
This study investigates the urgency of teaching connected letter writing in strengthening literacy among Grade IV students at SD Negeri 2 Waisai, Raja Ampat. The problem arises from the decline of cursive writing, instruction due to the dominance of digital technology, which has reduced students’ practice opportunities and weakened their ability to produce neat, legible writing. The research aims to examine the implementation of cursive writing instruction, assess students’ proficiency, and evaluate its necessity in enhancing literacy. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving teachers and students. Analysis followed the Miles and Huberman model with triangulation to ensure validity. The findings reveal that while teachers consistently integrate cursive writing into lessons, methods remain conventional and media support is limited. Students show varied proficiency: some achieve neat and fluent writing, while others struggle with consistency due to insufficient prior practice. Despite these challenges, teachers emphasize the strategic importance of cursive writing in supporting literacy, as it fosters fine motor development, fluency, and readability—critical elements for effective communication. The study concludes that cursive writing is not merely a technical skill but a fundamental component of literacy development. However, limitations include the focus on a single school in a remote 3T area, restricting generalization.